2024
DOI: 10.1002/imt2.174
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of potentially novel species expands the genomic and functional diversity of Lachnospiraceae

Xiaoqian Lin,
Tongyuan Hu,
Zhinan Wu
et al.

Abstract: The Lachnospiraceae family holds promise as a source of next‐generation probiotics, yet a comprehensive delineation of its diversity is lacking, hampering the identification of suitable strains for future applications. To address this knowledge gap, we conducted an in‐depth genomic and functional analysis of 1868 high‐quality genomes, combining data from public databases with our new isolates. This data set represented 387 colonization‐selective species‐level clusters, of which eight genera represented multili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…In the present study, the results from the differential abundance analysis showed that, compared to the LCP and HCP diets, the LCP+W diet increased the abundance of Frisingicoccus and the F0058 genus. Frisingicoccus is a butyrate-producing bacteria member of the family Lachnospiraceae [ 60 ]. Interestingly, Frisingicoccus has been reported to be associated with gut health in humans, and in agreement with our findings, it is positively linked with body weights in pigs [ 61 ] and with high faecal scores, being depleted in the gut of dairy cows with diarrhoea [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results from the differential abundance analysis showed that, compared to the LCP and HCP diets, the LCP+W diet increased the abundance of Frisingicoccus and the F0058 genus. Frisingicoccus is a butyrate-producing bacteria member of the family Lachnospiraceae [ 60 ]. Interestingly, Frisingicoccus has been reported to be associated with gut health in humans, and in agreement with our findings, it is positively linked with body weights in pigs [ 61 ] and with high faecal scores, being depleted in the gut of dairy cows with diarrhoea [ 62 ].…”
Section: Discussionmentioning
confidence: 99%